Analisis Pengaruh Kecepatan Motor Dan Gaya Magnet Terhadap Kapasitas Produksi Pada Prototipe Mesin Pemisah Sampah Material Ferromagnetik Dan Non Ferromagnetik - Arief, Dodi Sofyan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
This research aims to analyze the influence of motor velocity and magnetic force upon the production capacity on the centrifuge prototype of the ferromagnetic and non-ferromagnetic material waste based on the calculation of production capacity, induced magnetic attraction, and the ratio of separated ferromagnetic material with non-ferromagnetic material. The research is experimental research with the numbers of sample ratio of ferromagnetic material waste is 50% and non-ferromagnetic waste is 50%. Based on the conducted tests and calculations, the results are 1) the maximum production on centrifuge prototype of the ferromagnetic metal waste and non-metal is 0.0313 kg/s, 2) the obtained magnetic electricity attraction is 5,75 N, and 3) The amount of ferromagnetic material that mostly separated from the mixture of ferromagnetic and non-ferromagnetic material waste in ferromagnetic tub is when the engine rotation indicates 20 rpm and the magnetic force indicates 4,85 N.Keywords: Belt Conveyor, Magnetic Electricity, Production Capacity